Impact of CSR, green finance and green innovation on environmental performance of banks in India - Meraj, Maryam (Managing global transitions, 2025)
In an era of growing environmental challenges, the role of banks in promoting sustainability is critical. This study examines how Corporate Social Responsibility (CSR), green finance, and green innovation influence the environmental performance of Indian banks. Guided by legitimacy theory and the natural resource-based view, survey data from 379 bank employees were analysed using structural equation modelling. The results reveal that robust CSR initiatives, effective green finance practices, and innovative green strategies significantly enhance banks’ environmental performance. These findings contribute to theoretical understanding and offer practical insights for improving sustainability in the banking sector. The study recommends that banks in emerging economies strengthen internal resources by investing in CSR, adopting green finance, and fostering green innovation to boost environmental performance. Such efforts align with global sustainability goals, positioning banks as key players in environmentalprotection and responsible finance.
Keywords: corporate social responsibility; družbena odgovornost podjetij; environmental performance of banks; green finance; green innovation; modeliranje strukturnih enačb; okoljska uspešnost bank; structural equation modelling; zelene inovacije; zeleno financiranje